Building the Future: The Role of Nurul 'Ilmi School in the Advancement of Science and Global Insight Through Literacy - AGUSTINA, NAIMAH (Education Achievement: Journal of Science and Research, 2024)
This essay discusses the important role of Nurul 'Ilmi School in developing a bright future with a focus on the advancement of science and global insight through literacy. This essay explores how Nurul 'Ilmi School has successfully promoted science and global insight as the main foundation for students in understanding and facing future challenges. In this context, this essay analyzes the strategies used by Nurul 'Ilmi School to create a learning environment that allows students to develop as competent and knowledgeable individuals in the fields of science and global insight. The results of this essay find the role of Nurul 'Ilmi School, namely using the following strategies; literacy as a foundation for progress, instruments and motivation for science, expanding global insight and creating ideal leaders. Practically, this essay is expected to contribute to shaping the future of the young generation who are ready to be involved in advancing science and have a global insight.